Hypothalamic ER stress: A bridge between leptin resistance and obesity. Issue 14 (23rd April 2015) - Ramírez, Sara; Claret, Marc
Abstract : The prevalence of obesity has increased worldwide at an alarming rate. However, non‐invasive pharmacological treatments remain elusive. Leptin resistance is a general feature of obesity, thus strategies aimed at enhancing the sensitivity to this hormone may constitute an excellent therapeutical approach to counteract current obesity epidemics. Nevertheless, the etiology and neuronal basis of leptin resistance remains an enigma. A recent hypothesis gaining substantial experimental support is that hypothalamic endoplasmic reticulum (ER) stress plays a causal role in the development of leptin resistance and obesity. The objective of this review article is to provide an updated view on current evidence connecting hypothalamic ER stress with leptin resistance. We discuss the experimental findings supporting this hypothesis, as well as the potential causes and underlying mechanisms leading to this metabolic disorder. Understanding these mechanisms may provide key insights into the development of novel intervention approaches.